Association Between Serum Galectin-3 Levels and Coronary Stenosis Severity in Patients With Coronary Artery Disease - Li, Mingxing; Guo, Kai; Huang, Xuansheng; Feng, Li; Yuan, Yong; Li, Jiewen; Lao, Yi; Guo, Zhigang (Frontiers in Cardiovascular Medicine, 2022)
Background The relationship between galectin-3 (Gal-3) and coronary artery disease (CAD) has not been fully elucidated. Aim This study aimed to determine the relationship between the presence and severity of CAD and serum Gal-3 levels. Patients and Methods Three-hundred thirty-one consecutive CAD patients were enrolled as the study group. An additional 62 patients without CAD were enrolled as the control group. Serum Gal-3 levels were separately compared between the non-CAD and CAD groups, among the stable CAD and Acute coronary syndrome (ACS) groups, and between CAD patients with low and high SYNTAX scores (SSs). The 1-year cumulative rate of major adverse cardiac events (MACEs) was also compared among ACS patients by Gal-3 levels. Results Serum Gal-3 was significantly higher in the CAD group than in the non-CAD group 3.89 (0.16–63.67) vs. 2.07 (0.23–9.38) ng/ml, P < 0.001. Furthermore, serum Gal-3 was significantly higher in the non-ST-segment elevation ACS (NSTE-ACS) group than that in the stable CAD group, 4.72 (1.0–16.14) vs. 2.23 (0.65–23.8) ng/ml, P = 0.04 and higher in the ST-segment elevation myocardial infarction (STEMI) group than that in the stable CAD group 7.87 (0.59–63.67) vs. 2.23 (0.65–23.8) ng/ml, P < 0.001. Serum Gal-3 level was an independent predictor of ACS compared with stable CAD group (OR = 1.131, 95% CI: 1.051–1.217, P = 0.001) as well as high SS (OR = 1.030, 95% CI: 1.021–1.047, P = 0.038) after adjust other confounding risk factors. Acute coronary syndrome patients with Gal-3 levels above the median (gal-3 = 4.78 ng/ml) showed a higher cumulative MACE rate than those with Gal-3 levels below the median. After adjusting other confounding risk factors, Gal-3 remained an independent risk factor for the cumulative rate of MACEs in ACS patients (6% higher rate of MACEs incidence per 1 ng/ml increment of Gal-3). Conclusion Galectin-3 correlated with the presence of CAD as well as coronary stability and complexity. Galectin-3 may be valuable in predicting mid-term prognosis in ACS patients.